Menggugah Kesadaran Berdemokrasi dalam Dunia Pesantren - Zainul Mushthofa; Siti Aminah (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2023)
Abstract: Pondok Pesantren is a traditional Islamic education dormitory where students live together and study under the guidance of a teacher (or more) known as Kyai. The dormitories for these students are located in a pesantren environment where the Kyai who is located also provides a mosque for worship, space for study, and other activities. Santri as a traveler seeking knowledge considers Kyai as a teacher who must be obeyed. Sometimes, because they live and live in a dormitory close to their Kyai, they also think of them as if they were their own father. On the other hand, Kyai considers his students as a mandate from God that must be protected. Apart from this spiritual relationship, in most pesantren with traditional patterns and/or ideas, the notion of pesantren is still developing as a small kingdom with a Kyai as king. Islamic boarding schools as educational and social institutions are always required to keep up with the times so that it is time for them to make changes by changing to a more democratic system. applied.